The protective effects of epigallocatechin-3-gallate (EGCG) on hydrogen peroxide-induced oxidative damages in Saccharomyces cerevisiae - Beyaz, Seda; Gok, Ozlem; Can, Muhammed Ismail; Aslan, Abdullah (Mattioli 1885, 2021)
Epigallocatechin gallate (EGCG), one of the green tea ingredients, is a non-toxic catechin derivative and is an effective polyphenol in preventing tissue damage, cancer formation and increasing metabolic rate. Strong antioxidant property EGCG having anti-inflammatory, antioxidant, antihypertensive, antimicrobial, antiviral, antifungal, antitumor and various organs as well as neuroprotective effect of many convenience protection against ischemia-reperfusion injury. In this study, four groups were formed to investigate whether Epigallocatechin-3-gallate (EGCG) has a protective role against the damage caused by hydrogen peroxide (H2O2) in Saccharomyces cerevisiae. Groups: (i) Control Group; Yeast cultivated group only; (ii) EGCG Group: EGCG administered group (10 %); (iii) H2O2 Group: Group given H2O2 (15 mM); (iv) EGCG + H2O2 (15 mM) Group: Group given EGCG (10 %) + H2O2 (15 mM). S. cerevisiae cultures were developed at 30 degrees C for 1, 3, 5 and 24 hours (h). Cell growth, lipid peroxidation MDA (malondialdehyde) analysis and GSH (glutathione) levels were determined by spectrophotometer. Total protein changes were detected by SDS-PAGE electrophoresis and calculated by Bradford method. According to the results obtained, Cell growth (1, 3, 5 and 24 h), total protein synthesis and GSH levels (24 h) increased in EGCG groups, while MDA level decreased (24 h) when compared with H2O2 group. As a result, EGCG has been shown to have an effect that promotes cell growth and total protein synthesis as well as reducing oxidative damage in S. cerevisiae culture.
Keywords: EGCG; H2O2; oxidative damage; protein; Saccharomyces cerevisiae; SDS-PAGE